(3cJGH aj CUhd GdOjf YbGFO Cgd GdSfIs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3jHJOF HaUd ai MO GdfXQ s
(3BNQgG (B:s
(3ade JbJdhg dQLY CMO GdQShdjf Edi GdMb hGYJQa HdRhe GdMLI hYGO GdBNQ Edi bheg JeJ HMeO Gddg hefg hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3JHUQGJ GdCUd (B:s
Keywords: (3CUhd Gdabgs